The influence of an eight month multicomponent training program in edlerlies gait and bone mineral mass - Monteiro, A.M. (2018)
Aging induces neuromuscular changes and mass, strength, muscular resistance and power, motor coordination, so, reaction and movement speed reduction may be compromised [1]. These changes result in slower movements and functional limitations in gait and weight transfer activities [1]. Even more, the functional fitness decreasing due to aging, increases the risk of falls and bone fractures [2], reducing the elderly’s quality of life. Objective Thus, the aim of this study was to assess the influence of an eight months multicomponent training program in elderly’s gait and bone mineral mass (BMM). Methods Forty-nine elderlies were recruited for this research with 64.39 (± 6.33) years old, 11 males with 67.45 (± 4.93) and 38 females with 63.50 (± 7.47) years old. The subjects were community living persons of Bragança. All procedures carried out in this research were in accordance to the Declaration of Helsinki. The multicomponent training program followed the Carvalho et al. [1], recommendations. Each session time volume was between 50 to 60 minutes. The sessions were divided in five parts: 1) general warm-up; 2) walking with aerobic exercises; 3) 1 to 3 sets of exercises of muscular resistance with 12 to 15 repetitions; 4) Static and dynamic balance training; 5) An active recovery period with stretching and breading exercises. The elderlies gait was evaluated with Berg Balance Scale (BBS) and BMM with bioimpedance (Tanita, BC-545). The Wilcoxon-Mann- Whitney test allowed to assess the differences between pre and post 8 months of the training program in BBS and BMM. The tests were performed with a significant level of 5%. Results The BBS values pre and post the multicomponent training program for BBS were 47.33 and 50.33 respectively. In BMM, the pre and post values were 2.36kg and 2.39 kg. Despite the differences in BMM means, they were not significant between the two moments (F = 1.253; p = 0.706). However, the same did not occur in terms of BMS values (F = 1.967; p< 0.001), where gait values increased significantly in the second moment. Conclusions Although the multicomponent training program did not increase the BMM in the elderly subjects, gait values increased significantly. Thus, it is possible to conclude that, the training program significantly improved the elderlies’ gait and quality of life.